Síntese e avaliação biológica de novos derivados do sistema tieno[2,3-b]piridina - Pinheiro, Luiz Carlos da Silva (2007)
This work describe the synthesis of new 54 Thieno[2,3-b]pyridine derivatives. The chosen methodology for the synthesis of these compounds involves the condensation reaction of the bis-(2-thienylammonium)hexachlorostannate with ethyl (ethoxymethylene)cyanoacetate to produce ethyl a-cyano-b-(N-2-thienylammonium)acrylate. This acrylate derivative was submitted to thermal cyclization with dowtherm, followed by chlorination with phosphorus oxychloride, resulting in 4-Chlorothieno[2,3-b]pyridine-5-carbonitrile derivative, which were submitted to nucleofilic substitution reaction with different anilines, producing 13 new 4-(Phenylamino)thieno[2,3-b]pyridine-5-carbonitrile (I a-m) derivatives, with yields of 70 to 96%. From the compounds (I a-m) 13 new 5-(4,5-Dihidro-1H-imidazol-2-yl)-4-(phenylamino)thieno[2,3-b]pyridine (II a-m) derivatives were obtained with yields of 85 to 60%; 13 new 5-(1H-tetrazol-5-yl)-4-(phenylamino)thieno[2,3-b]pyridine (III a-m) derivatives, in good yields. New 9 4-(Phenylamino)thieno[2,3-b]pyridine-5-carboxylic acid (IV a-c, f, g, i-k, m) derivatives were prepared, with yields 75% - 65%, from acid hydrolysis of (I a-c, f, g, i-k, m) that showed to be more efficient than alkaline hydrolysis.The alkaline hydrolysis reaction of the (I j) derivative at 180º C, resulted in one unknown decarboxylated compound 4-(3 -Chorophenylamino)thieno[2,3-b]pyridine (IV j). Five compounds of the new tetracyclic ring system benzo[b]thieno[3,2-h]-1,6-naphthyridines (V a, c, i, k, m) were synthesized from the acid (IV a, c, i, k, m) derivatives, with yields of 70 to 75%. In the antiviral evaluation of 4-Phenylamino)thieno[2,3-b]pyridine-5-carbonitriles (I a, c, f, g-i, m), the compound If showed 99% of activity against virus HSV-1 at 50 µM. The evaluation antiparasiter against Giárdia Lamblia, indicates that the system Thieno[2,3-b]pyridine showed presents a significant antiparasiter effect, detaching the derivative I e, with 88% of inhibition at 50 µM. The 5-(4,5-Dihidro-1H-imidazol-2-yl)-4-(phenylamino)thieno[2,3-]pyridines (II am) derivatives and 5-(1H-tetrazol-5-yl)-4-(phenylamino)thieno[2,3-b]pyridines (III a-m) also had presented activity front the parasite Giárdia Lamblia, inhibiting the growth of the parasite in 24 hours of incubation, with 70% of activity, indicating a pharmacological model that must widely be investigated aiming at the composite development new against the Giardíase. The antibacterial evaluation of 5-(4,5-Dihidro-1H-imidazol-2-yl)-4- (phenylamino)thieno[2,3-b]pyridines (II a-m) and 5-(1H-tetrazol-5-yl)-4- (phenylamino)thieno[2,3-b]pyridines (III a-m), showed that the compound III j was the most effective of this series (MIC de 64 µg/mL)